2007
DOI: 10.1007/s10792-007-9176-0
|View full text |Cite
|
Sign up to set email alerts
|

Early OCT changes of neuroretinal foveal thickness after first versus repeated PDT in AMD

Abstract: Early change in NFT, demonstrated on OCT, indicates that PDT causes different retinal response in primary versus repeated treatment of PDT for CNV due to AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…7-10 However, frequent persistence and recurrence of CNV, which require multiple treatments and are associated with poor long-term visual outcomes, are major limitations. 34,35 Recent studies have demonstrated that PDT causes selective photothrombosis but it also produces inflammatory effects with delivery of local proangiogenic factors. Upregulation of VEGF may explain the high recurrence rate of CNV (nearly 98%) within 3 months following PDT.…”
Section: Commentmentioning
confidence: 99%
“…7-10 However, frequent persistence and recurrence of CNV, which require multiple treatments and are associated with poor long-term visual outcomes, are major limitations. 34,35 Recent studies have demonstrated that PDT causes selective photothrombosis but it also produces inflammatory effects with delivery of local proangiogenic factors. Upregulation of VEGF may explain the high recurrence rate of CNV (nearly 98%) within 3 months following PDT.…”
Section: Commentmentioning
confidence: 99%